Estudo de arenitos através de processos estocásticos de reconstrução 3d em meios fractais e percolativos - Amaral, Leonardo Aguiar do (2015)
This work aims to investigate morphology of porous materials through digital image re-construction techniques. Specifically, we will use statistical analysis processes to performa 3-D reconstruction, which means making a three-dimensional estimate of a porous struc-ture through a single 2-D image of the sample. This is done through 2-D reconstructionmethods involving the application of stochastic processes on 2-D images of a sample togenerate various other images, too 2-D, which retain some of the topological features of theoriginal image. The next step, called 3-D reconstruction performed stacking these imagesto obtain a three dimensional structure that also maintains these characteristics, we cite asan example: porosity, correlation points, grain size and pore distribution, among others.Recent publications indicate that the digital image processing of the porous sample havebeen shown to be an excellent alternative to traditional methods of analysis, it ensures goodreproducibility, reduces costs and processing time as well as providing topological informa-tion of the sample. Although the techniques discussed in this paper are applicable to porousmaterials in general, our studies focus on the investigation of a particular material calledSandstone, which will be conducted simulations in some 2-D images of samples publishedin scientific articles in the field for later comparison results. Porous materials, in general,may be considered complex and cluttered means whose formation takes place randomly, sowe will also discuss how percolation theory and fractal can contribute to the improvementof reconstruction techniques